P-glycoprotein positive, drug resistant invasive lymphoepithelial thymoma: treatment response to chemotherapy with cyclosporin and quinine. Issue 7 (July 1995) - Gala, J L; Noël, H; Rodhain, J; Ma, D F; Ferrant, A
Abstract : A case of invasive drug resistant thymoma, expressing P-glycoprotein, which showed noticeable clinical response to chemotherapy and the multidrug resistance modulating agents cyclosporin and quinine is reported. A 46 year old man presented with severe left shoulder pain and a diagnosis of invasive lymphoepithelial thymoma was made following chest x ray and a computed tomography scan. The patient underwent extensive chemotherapy without resolution of the tumour. More than 90% of the malignant epithelial cells were strongly positive for P-glycoprotein and based on this observation, cyclosporin and quinine were added to the chemotherapy regimen. The mediastinal mass completely resolved and the size of the pleural metastasis decreased substantially. The patient, however, died of an intercurrent infection. This case report highlights the feasibility and efficacy of using cyclosporin and quinine in combination with VAD chemotherapy in the treatment of invasive thymoma.